Comparative Analysis between the Shinyei PPD42NS and Plantower PMS7003 Low-Cost Air Quality Sensors - Ong, Camron Evan C. (Animo Repository, 2021)
Particulate matter (PM) is a form of air pollution that is considered harmful as these may cause respiratory problems. PM sensors are used to measure PM in the air and vary in costs. There have been many studies done on the accuracies of these sensors based on their price. In this research, a comparative analysis was done between a low-cost sensor, the Shinyei PPD42NS, and a mid-range sensor, the Plantower PMS7003. In previous studies, there were comparisons made between low quality sensors but no direct comparison between these two sensors. The tests were done in an indoor and outdoor environment wherein sensors were placed beside each other to measure particulate matter greater than 1 micron for a continuous span of 10 hours. Results from these tests showed that the Shinyei measurements broadly follow the more expensive Plantower but have more significant deviations over short periods. Larger deviations were noted in the morning and evening periods of testing. Recommendations for further characterization are provided in this paper.